PTH-081 Incidence and long term implications of pre pouch ileitis. (17th June 2017) - Segal, J; Mclaughlin, S; Clark, S; Faiz, O; Hart, A
Abstract : Introduction: Restorative proctocolectomy (RPC) is considered the procedure of choice in patients with ulcerative colitis (UC) refractory to medical therapy. Pre-pouch ileitis (PPI) has no standard definition but is characterised by the presence of mucosal inflammation of the ileum immediately proximal to the pouch. This pattern of inflammation can extend into the afferent limb up to 50 cm. The estimated incidence of PPI is 6% and long-term follow-up data is lacking. Method: We followed up our original cohort of patients who were diagnosed with PPI that was published in 2009. Patients were followed up until last available clinic or at the point of pouch failure defined as permanent ileostomy, revision of pouch or refashioning of pouch. Demographics were collected including biological use, smoking status, stool frequency, presence of terminal ileal (TI) inflammation prior to colectomy and previous obstructive symptoms. Baseline endoscopic findings at diagnosis, treatment at diagnosis and symptoms at diagnosis were collected. Follow-up data collected was stool frequency, endoscopic findings, treatment at follow-up and overall pouch function. Results: The median length of follow-up from the index pouchoscopy of the 31 patients with PPI was 98 (range 27–143) months. Seven (23%) patients who had an index pouchoscopy with PPI had an end ileostomy; five (71%) of these were due to chronic pouchitis symptoms and two (29%) were due to small bowel obstruction secondary to pre-pouch strictures. The median time from RPC to end ileostomy was 132 (range 24–276) months in these patients. The initial presence of PPI was associated with persistent use of antibiotics to treat co-existing pouchitis at long term follow-up. Of the 24 patients who retained their pouch, 22 (92%) of these required antibiotics at some point with 16 (73%) patients requiring chronic antibiotic use to help alleviate their symptoms. All 31 patients had co-existing pouchitis. One patient was reclassified as having Crohn's disease. The median time from RPC to end ileostomy was 132 (range 24–276) months in these patients. All 31 patients had co-existing pouchitis. One patient was reclassified as having Crohn's disease. Conclusion: In our cohort PPI is almost exclusively found in patients with pre-existing pouchitis. The presence of PPI is associated with a high chance of pouch failure. PPI does not appear to be a feature of Crohn's disease at long term follow-up. References: . McLaughlin SD. et al. Incidence and short-term implications of prepouch ileitis following restorative proctocolectomy with ileal pouch-anal anastomosis for ulcerative colitis. Dis. Colon Rectum2009;52:879–83. . Bell, A J. et al. Pre-pouch ileitis: a disease of the ileum in ulcerative colitis after restorative proctocolectomy. Colorectal Dis 2006;8:402–10. Disclosure of Interest: None Declared